Inheritance of evolved clethodim resistance in Lolium rigidum populations from Australia. Issue 8 (4th January 2017) - Saini, Rupinder Kaur; Malone, Jenna; Gill, Gurjeet; Preston, Christopher
Abstract: BACKGROUND: In Australia, the extensive use of clethodim for the control of Lolium rigidum has resulted in the evolution of many clethodim‐resistant L. rigidum populations. Five clethodim‐resistant populations of L. rigidum were analysed for the inheritance of clethodim resistance. RESULTS: Reciprocal crosses were made between resistant (R) and susceptible (S) populations. Within crosses, dose–responses of reciprocal F1 families of all populations except A61 were similar to each other, indicating that clethodim resistance in these populations is encoded on the nuclear genome. The level of dominance observed in the dose–response experiments ranged from partial to complete within the herbicide rate used. In the A61 population, within each cross, the response of F1 from the maternal and paternal parent was different, indicating that resistance is inherited through the female parent. All backcross populations segregated in a different manner. Only one population, FP, fitted a single‐gene model (1:1). Two populations fitted two‐gene models: a 3:1 inheritance model for F4 and a 1:3 inheritance model for A91. For population E2, no clear pattern of inheritance was determined, suggesting more complex inheritance. CONCLUSION: The results of this study indicate that different patterns of clethodim resistance in L. rigidum exist. © 2016 Society of Chemical Industry